Using Fuzzy Set as a Controller on the Lateral Dynamic of Autopilot to Reducing the Effect of the Atmospheric Disturbance - Saleh, Muna Hadi; Raheem, Noor Abdul Razzaq (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
In this paper, used fuzzy set as a controller to control roll and yaw angles in lateral dynamic of the autopilot system for jet transport using MATLAB/SIMULINK. Autopilot systems are complex devices that demand exact control and stability. In this paper explained the lateral dynamic on automatic pilot and studied the effect of atmospheric disturbances on the stability then designed the fuzzy set controller to reduce three type of disturbance which faced the pilot during the flight.